Big Data Service of Financial Law Based on Cloud Computing - Li, Yaqian (Big Data Analytics for Cyber-Physical System in Smart City, 2021)
With the explosive growth of data volume in the field of financial law, how to fully tap the effective value of big data, how to deal with big data computing tasks in a timely and fast manner, to provide users with high-value and high-efficiency services, has become a problem that needs in-depth study. The impact of the legal environment on financial development and their interaction, empirical research, and reference to a large number of financial professional data, the financial legal environment under different legal systems for the actual impact of financial development are described. In the era of big data, the processing model and application technology of financial legal analysis service are facing new challenges. It is urgent to further study the service model, combination method, and big data processing technology to meet the needs of service value and timeliness. This paper first designs the model, processing flow, and system framework of financial big data analysis service, and then studies the combination method of multi-perspective learning and the key technology of task scheduling, On this basis, a big data analysis service system of securities is realized, and the financial supervision, financial law enforcement, judicial and financial legal services are fully used to improve the financial legal environment.